Role of electrokinetic parameters on asymmetric ultrafiltration membrane flux and rejection during separation of bovine serum albumin - Siti Marni, Aziz (2008)
The protein concentration involves the removal of solvent (usually water) from protein solution. There will be various methods that can be used for this protein concentration process. One of the methods is by using ultra filtration method. During ultra filtration, the macromolecules such as protein are retained on the membrane. The main objective in this experiment is to determine the optimum pH condition and ionic strength concentration which is give maximum permeate flux which is through the membrane. The molecular weight cut off for the membrane is 50 kDa. This study is carried out in order to know the effect of pH protein solution to the permeate flux and the percent rejection of protein molecules with the various value of pH. Besides, the effect of ionic strength concentration to the permeate flux and rejection protein molecule also had been highlight in this study. From the result acquire, optimum flux for BSA protein filtration is been observed in pH 8 solution and in 0.5M NaCl ionic strength concentration.